The biomechanical effects of stapes replacement by prostheses on the tympano-ossicular chain - Gentil, Fernanda (2019)
Hearing is a sequence of processes in which the ear translates sound waves into electrical signals, which are then sent to the brain where they are interpreted as sound. The ossicular chain of the middle ear is formed by three ossicles (malleus, incus, and stapes), of which the last and smallest, the stapes, vibrates, thus communicating with the inner ear through the stapes footplate. When abnormal bone formation immobilizes the stapes (otosclerosis), the passage of sound does not correctly occur and hearing can be compromised. In most cases, surgery is an option for its treatment. The stapes is totally or partially replaced by a prosthesis (stapedectomy or stapedotomy, respectively) allowing the passage of sound to the inner ear. This work presents a study on the behavior of different stapes prostheses, considering their biomechanical characteristics. The stapes was replaced by different prostheses, made of dissimilar materials: stainless steel, teflon, and titanium. The umbo and stapes footplate displacements for the models with these prostheses were obtained and compared with the displacements obtained with the model representative of the normal ear. In the models with prostheses, the displacements are found in the hole where the prosthesis is attached.